ANALISIS PENERAPAN PERNYATAAN STANDAR AKUNTANSI KEUANGAN (PSAK) NOMOR 109 TENTANG AKUNTANSI ZAKAT DAN INFAQ/SEDEKAH PADA BADAN AMIL ZAKAT DAERAH DI KABUPATEN ACEH TENGGARA - Ruhmana Syakinah; Afrah Junita; Muhammad Salman; Rahmad Tantawi (Jurnal Mahasiswa Akuntansi Samudra, 2021)
This research was conducted in Baitul Mal, Southeast Aceh Regency. This study aims to analyze the suitability of recording and acknowledging cash transactions of Zakat and Infaq/Alms funds at the Baitul Mal, Southeast Aceh Regency based on the Statement of Financial Accounting Standards (PSAK) Number 109. The analytical method in this study uses a comparative descriptive analysis method with data collection methods through interviews. and documentation. The results of this study indicate that the application of Zakat and Infaq/Alms accounting in Baitul Mal, Southeast Aceh Regency is not in accordance with the Statement of Financial Accounting Standards (PSAK) Number 109 concerning Zakat and Infaq/Alms, this is indicated by the absence of presentation of components of financial statements that complete based on PSAK Number 109, namely the statement of financial position (balance sheet), reports on changes in funds, reports on changes in assets managed, reports on cash flows, and notes to financial statements, but only presents simple financial statements, namely reports on the collection and distribution of zakat and infaq/alms funds.